Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1002/srin.201500210
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Inflow Rate Variation on Intermixing in a Steelmaking Tundish during Ladle Change‐Over

Abstract: The intermixing of dissimilar grades of steel in tundish during the ladle change-over is a problem of growing interest. During sequential casting of different grades, it is important that the intermixing of the grades is kept to a minimum. Present work deals with computational and water model studies of the three-dimensional turbulent fluid flow in a multi-strand tundish during ladle change-over process. The physical investigation has been carried out by conducting experiment on a 1:4 scale model of tundish. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…1 The vast application of steel makes it production process important aspect of study. [2][3][4][5] The cleanliness of steel is a most required process of industry. 6 Various methods have been used to enhance the properties of steel during solidification.…”
Section: Introductionmentioning
confidence: 99%
“…1 The vast application of steel makes it production process important aspect of study. [2][3][4][5] The cleanliness of steel is a most required process of industry. 6 Various methods have been used to enhance the properties of steel during solidification.…”
Section: Introductionmentioning
confidence: 99%
“…In the present numerical modeling, modified High-Resolution Interface Capturing (HRIC) [34] scheme was used due to its better interface approximation and stability of the solution. The F-curves obtained from numerical models have been compared with the experimental results and further discussion on F-curves can be referred to from the authors that previously published a research article [20]. It was demonstrated that the numerical model was capable to reproduce the water-based laboratory results.…”
Section: Comparison Of Interface Schemesmentioning
confidence: 99%
“…A correlation was developed to quantify the formation of mixed grade steel. Siddiqui and Jha [20] reported that the inflow rate has a significant impact on grade mixing in tundish during sequential castings. Cwudzinski [21] carried out a numerical investigation of flow control devices in tundish to modify the hydrodynamic pattern inside the tundish.…”
Section: Introductionmentioning
confidence: 99%
“…Different approaches are used and detailed in literature to minimize intermixing effects [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. They have been targeted at improving operating conditions and/or layout, even with suitable tools (e.g., particular ladle shroud geometry).…”
Section: Approachmentioning
confidence: 99%